Bibliometric Analysis of Global Research Trends on Ultrasound Microbubble: A Quickly Developing Field - Wu, Haiyang; Tong, Linjian; Wang, Yulin; Yan, Hua; Sun, Zhiming (Frontiers in Pharmacology, 2021)
Background: Microbubbles are widely used as highly effective contrast agents to improve the diagnostic capability of ultrasound imaging. Mounting evidence suggests that ultrasound coupled with microbubbles has seen promising therapeutic applications in cancer, cardiovascular and neurological disorders by acting as gene or drug carriers. The aim of this study was to identify the scientific output and activity related to ultrasound microbubble through bibliometric approaches. Methods: The literatures related to ultrasound microbubble published from 1998 to 2019 were identified and selected from the Science Citation Index Expanded of Web of Science Core Collection (WoSCC) on February 21, 2020. The Scopus database was also searched to validate the results and provided as supplementary material. Quantitative variables including number of publications and citations, H-index, journal citation reports were analyzed by Microsoft Excel 2019 and GraphPad Prism 8.0 software. VOS viewer and CiteSpace V were used to perform co-authorship, co-citation and co-occurrence analysis for countries/regions, institutions, authors, and keywords. Results: A total of 6088 publications from WoSCC were included. The USA has made the largest contribution in this field, with the majority of publications (2090, 34.3%), citations (90741, 46.6%), the highest H-index (138) and closely collaborations with China and Canada. The most contributive institutions were University of Toronto. Professors De Jong N and Dayton P A have made great achievements in this field. However, the research cooperation between institutions and authors were relatively weak. All the studies could be divided into four clusters: “ultrasound diagnosis study” “microbubbles’ characteristics study”, “gene therapy study”, and “drug delivery study”. The average appearing years (AAY) of keywords in cluster “drug delivery study” was more recent than other clusters. For promising hotspots, “doxorubicin” showed a relatively latest AAY of 2015.49, followed by “nanoparticles”, “breast cancer”. Conclusion: There has been an increasing amount of scientific output on ultrasound microbubble according to the global trends, and the USA stay ahead in this field. Collaboration between research teams still needs to be strengthened. The focus gradually shifts from “ultrasound diagnosis study” to “drug delivery study”. It is recommended to pay attention to the latest hotspots, such as “doxorubicin”, “nanoparticles”, and “breast cancer”